Growth and Yield of Rice Planted in a Tidal Soil Under NPK in situ and Cow Manure Application - Budianta, Dedik; Alfredo Lee Panggar Bessy, Jerry; Hermawan, Agus (UNIVERSITY OF LAMPUNG, 2021)
The specific location fertilization or in situ fertilization rate is a dynamic application and management method dynamically adapted to the plantâ€™s need according to location and season related to soil chemical properties and aims to increase farmer profit. This greenhouse experiment aimed to evaluate the NPK fertilizer dose based on in situ soil chemistry of tidal swamp compared to NPK recommendation combined with cow manure from the local farm. These pot experiments were conducted from June to October 2019 in a Greenhouse of Soil Science Department, Faculty of Agriculture, Sriwijaya University, Indralaya, Ogan Ilir of South Sumatra.Â This experiment used a factorial completely randomized design with two factors and three replications. The first factor was NPK fertilizer rate consisting of two levels (200 kg ha-1 Urea, 100 kg ha-1 SP-36, and 100 kg ha-1 KCl) from recommended fertilizer, and (102 kg ha-1 Urea, 0 kg ha-1 SP-36, and 66 kg ha-1 KCl) from the in situ soil analysis. The second factor was cow manure with four levels (2, 6, 8, and 10 Mg ha-1). The result showed that recommended NPK combined with 10 Mg ha-1 cow manure was the best for rice production in tidal lowland and produced 2.5 Mg ha-1.Â However, this result was not significant compared to NPK specific locations combined with the same rate of cow manure.